Pekhanjangan Money as a Sanction for Singkil Aceh's Customary Marriage in Review of Maqasid Syariah - Muslihun; Maysarah; Ali Shah, Syed Ahmad (Dirasah International Journal of Islamic Studies, 2025)
The phenomenon of pekhanjangan money as a customary sanction in the marriage of the Singkil Aceh Tribe creates a dilemma between the fulfillment of the right to marry and customary obligations. This tradition requires the bride-to-be to compensate her unmarried brother before the wedding. This research aims to analyze the practice of pekhanjangan money and its relevance to maqasid sharia, especially in the aspects of maintaining religion, soul, offspring, mind, and property. The research method uses a qualitative approach with the type of case study in three sub-districts of Aceh Singkil District. Data were collected through in-depth interviews with 15 informants (traditional leaders, religious leaders, perpetrators, and recipients of pekhanjangan), participant observation in three marriage cases, and documentation studies. Data were analyzed using the Miles and Huberman interactive model. The results showed that the practice of pekhanjangan is still strongly implemented with a flexible system, where the value of compensation can be negotiated according to economic capacity, ranging from one mayam of gold to other forms of compensation. From the maqasid sharia perspective, this practice supports the maintenance of the soul and intellect through its function in maintaining family harmony and mental health. However, implementation adjustments are needed so as not to cause excessive hardship for the less well-off parties and remain in line with sharia principles.